Biochemical study of the effect of stress conditions on the mandelonitrile‐associated salicylic acid biosynthesis in peach. (12th December 2019) - Bernal‐Vicente, A.; Petri, C.; Hernández, J. A.; Diaz‐Vivancos, P.
Abstract: Salicylic acid (SA) plays a central role in plant responses to environmental stresses. In a recent study, we suggested a third pathway for SA biosynthesis from mandelonitrile (MD) in peach plants. This pathway is an alternative to the phenylalanine ammonia‐lyase pathway and links SA biosynthesis and cyanogenesis. In the present work, using biochemical approaches, we studied the effect of salt stress and Plum pox virus (PPV) infection on this proposed SA biosynthetic pathway from MD. Peach plants were submitted to salt stress and Plum pox virus (PPV) infection. We studied the levels of SA and its intermediates/precursors (phenylalanine, MD, amygdalin and benzoic acid) in in vitro shoots. Moreover, in peach seedlings, we analysed the content of H2 O2 ‐related enzymes, SA and the stress‐related hormones abscisic acid and jasmonic acid. We showed that the contribution of this SA biosynthetic pathway from MD to the total SA pool does not seem to be important under the stress conditions assayed. Nevertheless, MD treatment not only affected the SA content, but also had a pleiotropic effect on abscisic acid and jasmonic acid levels. Furthermore, MD modulates the antioxidative metabolism via SA‐dependent or ‐independent redox‐related signalling pathways. Even though the proposed SA biosynthetic pathway seems to be functional under stress conditions, MD, and hence cyanogenic glycosides, may be operating more broadly than by influencing SA pathways and signalling. Thus, the physiological function of the proposed SA biosynthetic pathway remains to be elucidated. Abstract : Mandelonitrile, a recently proposed salicylic acid precursor, treatment affect stress‐related hormones level and redox‐related signaling pathways in peach.